Ciri Morfosemantik Afiks Derivasional Ber- dalam Konstruksi Verba Deajektival Bahasa Indonesia - Danang Satria Nugraha (Balai Bahasa Sulawesi Selatan, 2023)
The Indonesian language has a unique grammatical construction for verbs, which is the product of a derivational process that results in a deadjectival verb (VDaj). These VDaj constructions are morphologically marked by the affix ber-. This affix is commonly utilized in the Indonesian language and can be found, for instance, in the form of berberat hati, berbulat hati, and berputih hati. A recent study aimed to identify and describe the affix ber- use in VDaj construction as a phenomenon of morphosemantics. The study utilized data in Indonesian sentences in which the affix ber- of VDaj had been structured as one of its constituents. The data sources for this study were the Indonesian-Leipzig Corpora Collection (ILCC) and Kamus Besar Bahasa Indonesia (KBBI), and the data was obtained using the technique of textual documentation. The study analysis was done using the immediate defragmentation technique and referential comparison of meaning in the light of Derivational Morphology and Derivational Semantics. The analysis resulted in two main findings. First, the study found that the morphosemantic features of affix ber- could be construed to some extent if the affix had been distributed with one of the adjectival types. Second, the study identified at least three specific features of the affix in the VDaj of bI: (a) to form the VDaj in the type of STATE VERB, (b) to incorporate the semantic role of BENEFACTIVE in the argument of VDaj, and (c) in a narrow condition to create the RECIPROCAL meaning of VDaj. Overall, this study sheds light on the unique characteristics of the Indonesian language and provides valuable insights into the morphosemantic features of the affix ber- in VDaj construction. AbstrakVerba deajektival (VDaj) bahasa Indonesia (bI) merupakan salah satu struktur gramatikal yang dibentuk melalui derivasi. Kostruksi VDaj berpemarkah ber- merupakan struktur yang cenderung lazim dijumpai pada penggunaan bI, misalnya berberat hati, berbulat hati, dan berputih hati. Kajian ini bertujuan untuk memerikan karakter morfosemantis afiks ber- pada konstruksi VDaj bI tersebut. Data kajian ini berwujud kalimat bI yang berkonstituen konstruksi VDaj berpemarkah ber-. Sumber data kajian ini berwujud Indonesian – Leipzig Corpora Collection (ILCC) dan Kamus Besar Bahasa Indonesia (KBBI). Data dikumpulkan berdasarkan teknik catat atau dokumentasi tekstual. Data dianalisis berdasarkan teknik Bagi Unsur Langsung dan teknik Padan Referensial dengan mengacu pada teori Morfologi Derivasional dan Semantik Derivasional. Hasil analisis terdiri atas dua temuan sebagai berikut. Pertama, karakter morfosemantik afiks ber- pada konstruksi VDaj tercipta hanya jika afiks tersebut berdistribusi secara serial bersama salah satu jenis ajektiva bI. Kedua, secara khusus, ditemukan sekurang-kurangnya tiga kecenderungan ciri morfosemantik afiks ber-, yaitu (a) menciptakan VDaj bertipe KEADAAN, (b) melekatkan status peran semantis PENGALAM pada argumen penyerta VDaj, dan (d) mewujudkan makna gramatikal VDaj RESIPROKAL secara terbatas.